Hardfacing process of Ni-WC on gray cast iron substrate using GMAW method - Rasidi, Mohd Kamarul Shaufi (2017)
Hardfacing process of nickel-tungsten carbide (Ni-WC) overlay using gas metal arc welding (GMAW) method has been applied on gray cast iron substrate and the effect on microstructure, macrostructure and hardness property of the deposited overlay has been investigated. In the automotive industry, burr formation defect is continuously occurred on the produced blanks of sheet metal shearing process caused by the wear of the trim cutter die. The problem is more profound when using gray cast iron die which possess low hardness property. Ni-WC is a very hard hardfacing material and has potential to be utilized as the hardfacing material on the gray cast iron die. The use of GMAW method for the purpose of the hardfacing process needs to be done attentively in the aspect of the heat input because the produced heat input of the process affects the microstructure of the overlay thus affecting the hardness property of the hardfacing overlay. The effect of process parameters on the hardness and microstructure of the overlay was studied because the parameters are related to the heat input of the process. The effect of process parameters on the overlay bead width and height was also studied because bead width and height are two of important aspects of a hardfacing overlay. Thermal cycle of the process was also studied as to understand the thermal cycle effect on the hardness and microstructure of the overlay. The effect of overlay beads overlapping percentage on the microstructure and hardness was studied as well as the overlapped region undergoes more thermal effect of the process. The process parameters were optimized for improving the overlay hardness as well as bead width and height. Response surface methodology (RSM) using Design Expert software was applied for the design of experiment (DOE) and process parameters optimization in this study. The proposed optimized parameters focusing on maximizing the hardfacing overlay hardness are having hardness values within the targeted range from 610 HV60 to 810 HV60. The WC particles content was concluded as not significant in affecting the hardness value of the overlay at macro level. Heat input of the process has direct correlation to the bead height and width of the overlay but indirect correlation to the hardness of the overlay. The temperature reading of the hardfacing process as high as 1351°C was recorded in the thermal cycle investigation and the temperature reading implies that such phases like borides and silicides could have formed in the overlay and dictating the overlay hardness value. Process optimization was done and the optimization focusing on maximizing the hardness value by the software suggested sets of parameters having reliability value close to 1. The suggested sets of parameters have potential to be employed for improving the hardness of the gray cast iron substrate surface.